1993
DOI: 10.1259/0007-1285-66-783-228
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a programme for reduction of radiographic doses and results achieved through increases in tube potential

Abstract: Experiences in implementation of a programme to reduce doses to patients from radiographic examinations are described. A preliminary survey of entrance doses for selected examinations, calculated from mean exposure factors, identified equipment and examinations requiring attention. Subsequently more detailed studies were carried out with thermoluminescent dosimeters (TLDs). Results were coordinated with the aid of a database, which was used to monitor the agreement between dose calculations and TLD measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 3 publications
2
17
0
1
Order By: Relevance
“…Some discrepancies were noted between the levels of reduction seen between the patient and phantom studies, but these were minor and such discrepancies have been reported elsewhere [19]. The reductions described in this study compare well with those of previous workers who explored raised kVps for spine radiography [6,7,20] and other X-ray examinations [10,11].…”
Section: Discussionsupporting
confidence: 81%
“…Some discrepancies were noted between the levels of reduction seen between the patient and phantom studies, but these were minor and such discrepancies have been reported elsewhere [19]. The reductions described in this study compare well with those of previous workers who explored raised kVps for spine radiography [6,7,20] and other X-ray examinations [10,11].…”
Section: Discussionsupporting
confidence: 81%
“…The prevalent intervals of tube potential are not the ones that provide the lowest ESDs. In a comprehensive analysis, the increase of tube potential, followed by reduction of exposure setting, can be a very efficient means of reducing the ESD, in agreement with the results of the other studies (6,21,(24)(25)(26). Although this procedure could be important when the optimization principle is implemented, it must be utilized with careful criteria in the health services, as the diagnostic information contained in the radiological image might not be impaired with the reduction in doses.…”
Section: Diagnostic Reference Levelssupporting
confidence: 82%
“…The same for LAT projection the kV p is higher and mAs is 181.9 mAs which is much higher than the other studies [12,14]. Martin et al [22] found that increasing tube potential by 8 -13 kV in lumbar and thoracic spine examinations resulted in a dose reduction of 26 -36 %.…”
Section: Resultsmentioning
confidence: 71%